Unraveling the bacterial composition of a coral and bioeroding sponge competing in a marginal coral environment - Mote, Sambhaji; De, Kalyan; Nanajkar, Mandar; Gupta, Vishal (Frontiers in Microbiology, 2025)
The newly described bioeroding sponge Cliona thomasi, part of the Cliona viridis complex, is contributing to coral decline in the central eastern Arabian Sea, the West Coast of India. While its morphological and allelopathic mechanisms in coral invasion are well investigated, the role of its microbial communities in spatial competition is underexplored. This study focuses on the coral Turbinaria mesenterina and sponge C. thomasi, both known for their distinct symbiotic associations with Symbiodiniaceae. A 16S rRNA V3–V4 amplicon next-generation sequencing approach, followed by processing through the DADA2 algorithm, was used to analyze the bacterial composition. The results showed higher bacterial richness and diversity in coral samples, identifying 30 distinct phyla, compared to 14 in sponge samples. The coral samples were dominated by Proteobacteria, Actinobacteria, Firmicutes, Cyanobacteria, Planctomycetes, Chloroflexi, and Patescibacteria, while Proteobacteria, Cyanobacteria, Planctomycetes, and Actinobacteria were dominant in the sponge. Enrichment analysis revealed higher dominance of Acidobacteria, Actinobacteria, Chloroflexi, Dadabacteria, Firmicutes, Fusobacteriota, and Patescibacteria in the coral samples, while the sponge samples showed enrichment for Cyanobacteria, Planctomycetes, and Bdellovibrionota. Beta-diversity analysis (PERMANOVA and nMDS) showed significant differences, with an average dissimilarity of 81.44% between sponge and coral samples (SIMPER). These differences highlight variations in microbial profiles between sponges and corals, competing in the same vulnerable environment. Exploring the microbiome aspect, therefore, may elucidate physiological and ecological functions of the holobiont while also representing a health status biomarker for corals, supporting their conservation.